2011
DOI: 10.1002/dys.426
|View full text |Cite
|
Sign up to set email alerts
|

Teacher knowledge of basic language concepts and dyslexia

Abstract: Roughly one-fifth of the US population displays one or more symptoms of dyslexia: a specific learning disability that affects an individual's ability to process written language. Consequently, elementary school teachers are teaching students who struggle with inaccurate or slow reading, poor spelling, poor writing, and other language processing difficulties. Findings from studies have indicated that teachers lack essential knowledge needed to teach struggling readers, particularly children with dyslexia. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
109
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 31 publications
15
109
0
1
Order By: Relevance
“…Dyslexia was first reported in 1896 in the British Medical Journal by a physician, W. Pringle Morgan [1], and, since that initial report, major medical journals including JAMA, the New England Journal of Medicine, and the Journal of Pediatrics have continued to publish research furthering the scientific understanding of dyslexia [2][3][4]. Given the scientific progress in understanding the epidemiology, cognitive basis, and neurobiology of dyslexia, it is surprising that ignorance of the condition persists [5]; such ignorance continues to result in faculty misperceptions of dyslexia. For example, the very common and physiologically based symptom of slow reading in dyslexia can be misinterpreted as slow thinking; a resulting need for additional time on tests can then be misperceived as trying to game the system.…”
Section: Commentarymentioning
confidence: 99%
“…Dyslexia was first reported in 1896 in the British Medical Journal by a physician, W. Pringle Morgan [1], and, since that initial report, major medical journals including JAMA, the New England Journal of Medicine, and the Journal of Pediatrics have continued to publish research furthering the scientific understanding of dyslexia [2][3][4]. Given the scientific progress in understanding the epidemiology, cognitive basis, and neurobiology of dyslexia, it is surprising that ignorance of the condition persists [5]; such ignorance continues to result in faculty misperceptions of dyslexia. For example, the very common and physiologically based symptom of slow reading in dyslexia can be misinterpreted as slow thinking; a resulting need for additional time on tests can then be misperceived as trying to game the system.…”
Section: Commentarymentioning
confidence: 99%
“…Recent findings, however, suggest that educators do not have adequate knowledge regarding dyslexia. Both pre-service and in-service teachers demonstrated inadequate knowledge about dyslexia, possessed inaccurate information, and embraced common misconceptions about dyslexia (Ness & Southall, 2010;Wadlington & Wadlington, 2005;Washburn et al, 2011).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Administrators were typically not included in these studies, although they did comprise part of the sample identified by Wadlington & Wadlington (2005). One study (Paradice, 2001) Studies evaluating educator knowledge of dyslexia consistently conclude that educators do not possess acceptable levels of knowledge (Aladwani, & Al Shaye, 2012;Leite, 2012;Wadlington & Wadlington, 2005;Washburn et al, 2011). Furthermore, the lack of dyslexia knowledge is not specific to any group of educators (e.g., classroom teachers, specialists, administrators).…”
Section: Teacher Knowledge Of Dyslexiamentioning
confidence: 99%
See 2 more Smart Citations